Understanding end-user adoption of an online climate resilience tool. Issue 124 (October 2021) - Collini, Renee C.; Heming, Mikaela C.; Mohrman, Christina F.; Daigle, Melissa T.; Fulford, Casey A.; Gauthier Lowry, Celina L.; Hanisko, Marian D.; Mikulencak, Steven; Price, Rhonda; Sempier, Tracie T.; Shepard, Christine; Underwood, William V.; et al.
Highlights: Gulf TREE, a climate resilience tool, saw differences in how it was adopted by different users. Academic and non-profit users appear to have other pathways for finding climate resilience tools. Many users appeared to use Gulf TREE between two and three times over the course of the year. Web tracking analytics, such as Google Analytics can be adapted to better estimate number of uses. Highly ranked usefulness, usability, and intention to use a tool did not guarantee tool adoption. Abstract: Increasingly, climate researchers are pressured to generate products and tools from their research that support informed decision-making for increased social and environmental resilience. Despite the goal of these tools to integrate climate science into decision-making, little follow-up study is conducted after climate resilience tools are released to understand their effectiveness or application. It is important as limited resources across federal, state, local, and private sectors are invested in the development of climate resilience tools to understand their efficacy at achieving their intended purpose(s). This study leveraged Gulf TREE, a climate resilience tool released in 2018, to assess diffusion and adoption by intended users for intended purposes. Strategic efforts to enhance Gulf TREE via stakeholder engagement during development and positive evaluations prior to tool release, suggested there would be a high rate of adoption across all potential end-users; however, an end-user's intention to use a tool does not guarantee implementation. To expand the body of knowledge around climate resilience tool development, diffusion, and adoption, the authors explored the following research objectives: 1) Assess if end-users are adopting Gulf TREE; 2) Assess if end-users are adopting Gulf TREE for the intended purpose of finding climate change resilience tools; 3) Assess if end-users from different stakeholder categories are adopting Gulf TREE similarly. The study successfully determined that the climate resilience tool, Gulf TREE, was being adopted for its intended purposes. There were not sufficient data for statistical comparisons of use between stakeholder categories; however, general trends provided some indication of different stakeholder types utilizing Gulf TREE with different frequencies and for different purposes. Further, the study identified variability among sectors for how Gulf TREE was integrated into their existing suite of tools, with federal government and Sea Grant stakeholders using Gulf TREE as their primary resource versus academia and non-profit who appeared to have alternatives on which they continued to rely. Finally, this study identified that usability and usefulness may not be good indicators of tool adoption. This study expands the limited peer-reviewed assessments of a climate resilience tool's use. Continuing to develop this body of knowledge will allow for a better understanding of what constitutes a successful or effective climate resilience tool, how to improve current and future climate resilience tools, and how to best utilize limited resources when attempting to integrate climate science into decision-making.